(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
The aim of the present study was to detect and identify acid fast bacilli (AFB) from slaughtered cattle in South Darfur state, Sudan. A total of 6680 bovine carcasses were examined for caseous lesions at different abattoirs in South Darfur State during 2007-2009. Four hundred specimens were examined for presence of AFB using microscopic and culture techniques. Isolated mycobacteria were identified with selected biochemical tests. Out of the 6680 bovine carcasses examined, 400 (6%) had caseous lesions; 145 of them (36.3%) revealed acid fast filaments whereas 22 (5.5%) were harboring tuberculous AFB. Out of the filamentous AFB, 26 isolates were identified as M. farcinogenes, 6 as M. senegalense whereas the 22 non-filamentous AFB were identified as M. bovis. The prevalence of caseous lesions was lower in this study compared to previous ones. There was a marked decrease in prevalence of filamentous AFB causing bovine farcy (2. 2%) compared to 7% that had been detected during the mid 1970s from the same region.